Associations between maternal overweight/obesity during pregnancy and body composition in young adult offspring - Rerkasem, Amaraporn; Lyons-Reid, Jaz; Namwongprom, Sirianong; Wongsrithep, Suthathip; Mangklabruks, Ampica; Phirom, Kochaphan; Rerkasem, Kittipan; Derraik, José G. B. (Frontiers in Public Health, 2024)
Background: Maternal obesity is associated with an increased risk of large-for-gestational-age births and childhood obesity. However, evidence on its potential associations with long-term offspring body composition remains limited. This prospective cohort study examined associations between maternal body mass index (BMI) during pregnancy and body composition in the young adult offspring.Methods: Participants were the offspring from a birth cohort in Chiang Mai (Thailand). Maternal BMI was assessed at the first antenatal clinic visit (≤24 weeks of gestational) in [1989][1990]. In 2010-2011, we followed up the offspring at approximately 20.5 years of age, assessing their body composition using wholebody dual-energy X-ray absorptiometry (DXA) scans. Associations between maternal BMI and offspring body composition were explored using unadjusted and adjusted analyses.We assessed 391 young adults (55% were females). Higher maternal BMI was associated with increased offspring fat mass and lean mass. In adjusted analyses, offspring of mothers with overweight/obesity exhibited total body fat percentage 1.5 (95% CI 0.1, 2.9; p=0.032) and 2.3 (95% CI 0.2, 4.5; p=0.036) percentage points higher than offspring of normal-weight and underweight mothers, respectively. Fat mass index was similarly higher: 0.9 kg/m 2 (95% CI 0.3, 1.5 kg/m 2 ; p=0.002) and 1.4 kg/m 2 (95% CI 0.5, 2.3 kg/m 2 ; p=0.002), respectively. However, no differences in visceral adiposity were detected.Conclusions: Higher maternal BMI during pregnancy was associated with increased adiposity in young adult offspring. Our findings suggest that the cross-generational transmission of maternal obesity-related traits is associated with increased offspring adiposity in the long term.